Domestic (re)infestation risk with the main vector Triatoma infestans increases with surrounding green vegetation and social vulnerability in the Argentine Chaco - Elias, Dario Ezequiel (2024)
Background Chagas disease, caused by Trypanosoma cruzi, is still a public health problem in Latin Americaand in the Southern Cone countries, where Triatoma infestans is the main vector. We evaluated the relationshipsamong the density of green vegetation around rural houses, sociodemographic characteristics, and domestic (re)infestation with T. infestans while accounting for their spatial dependence in the municipality of Pampa del Indiobetween 2007 and 2016.Methods The study comprised sociodemographic and ecological variables from 734 rural houses with no missingdata. Green vegetation density surrounding houses was estimated by the normalized difference vegetation index(NDVI). We used a hierarchical Bayesian logistic regression composed of fixed effects and spatial random effectsto estimate domestic infestation risk and quantile regressions to evaluate the association between surrounding NDVIand selected sociodemographic variables.Results Qom ethnicity and the number of poultry were negatively associated with surrounding NDVI, whereasovercrowding was positively associated with surrounding NDVI. Hierarchical Bayesian models identified that domesticinfestation was positively associated with surrounding NDVI, suitable walls for triatomines, and overcrowdingover both intervention periods. Preintervention domestic infestation also was positively associated with Qom ethnicity.Models with spatial random effects performed better than models without spatial effects. The former identifiedgeographic areas with a domestic infestation risk not accounted for by fixed-effect variables.Conclusions Domestic infestation with T. infestans was associated with the density of green vegetation surroundingrural houses and social vulnerability over a decade of sustained vector control interventions. High density of greenvegetation surrounding rural houses was associated with households with more vulnerable social conditions. Evaluationof domestic infestation risk should simultaneously consider social, landscape and spatial effects to controlfor their mutual dependency. Hierarchical Bayesian models provided a proficient methodology to identify areasfor targeted triatomine and disease surveillance and control.